A Concentration Theorem of $(\boldsymbol{R}, p)$-Anders on Hadamard Manifolds (Communications in Mathematical Research, 2021)
In this note, we prove a concentration theorem of $(\boldsymbol{R}, p)$-anders. As asimple corollary, one can prove that $(X, p)$-anders do not admit coarse embeddingsinto Hadamard manifolds with bounded sectional curvatures.